1995
DOI: 10.1002/0471142735.im0620s13
|View full text |Cite
|
Sign up to set email alerts
|

Immunoenzymetric Assay of Mouse and Human Cytokines Using NIP‐Labeled Anti‐Cytokine Antibodies

Abstract: This unit describes a general method for immunoenzymetric assay of mouse and human cytokines. The technique is based on use of two anti-cytokine monoclonal antibodies (MAbs), each specific for a spatially distinct determinant on the cytokine. One of these is a coating antibody, and the other is a derivatized detecting antibody. A support protocol describes chemical labeling of anti-cytokine monoclonal IgG antibodies with the NIP hapten group to produce the detecting antibody. Another support protocol describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…The immunomodulatory effect of tobacco smoke and its components have been well documented (Thomas et al, 1975;Ronchetti et al, 1990;Stone, 1992;Sopori et al, 1993;Abrams, 1995;Geng et al, 1995;El-Nawawy et al, 1996;Geng et al, 1996;Oryszczyn et al, 2000;Gilliland et al, 2001). In our previous studies we showed that prolonged exposure of OVA sensitized mice to ETS resulted in enhanced levels of serum IgE, IgG1, and blood eosinophils .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The immunomodulatory effect of tobacco smoke and its components have been well documented (Thomas et al, 1975;Ronchetti et al, 1990;Stone, 1992;Sopori et al, 1993;Abrams, 1995;Geng et al, 1995;El-Nawawy et al, 1996;Geng et al, 1996;Oryszczyn et al, 2000;Gilliland et al, 2001). In our previous studies we showed that prolonged exposure of OVA sensitized mice to ETS resulted in enhanced levels of serum IgE, IgG1, and blood eosinophils .…”
Section: Discussionmentioning
confidence: 69%
“…Sandwich ELISAs were done to measure IL5, IL10 and IFN-g as previously described (Abrams, 1995). Briefly, ELISA plates were coated with the appropriate anticytokine antibodies and incubated at 48C overnight.…”
Section: Cytokine Elisamentioning
confidence: 99%
“…Sandwich ELISAs were used to measure IL-4, IL-5, IL-10, and IFN-␥ as previously described (18). In brief, ELISA plates were coated with the appropriate anti-cytokine Abs (11B11, TRFK4, 2A5, and XGM1.2 for IL-4, IL-5, IL-10, and IFN-␥, respectively) and incubated at 4°C overnight.…”
Section: Cytokine Elisamentioning
confidence: 99%
“…The plates were read on an ELISA reader (Labsystems iEMS reader, Helsinki, Finland). Abs for ELISAs were purified from serum-free hybridoma supernatants as previously described (18).…”
Section: Cytokine Elisamentioning
confidence: 99%
“…A standard curve was generated to determine the cytokine concentration in each sample. 9,10 Detection of residual BCL1 cells by adoptive transfer experiments An in vivo assay was used to detect residual BCL1 in the experimental mice as previously published. 11 A total of 10 5 lymphocytes obtained from a pool of spleen cells from each experimental group were adoptively transferred to untreated secondary BALB recipients.…”
Section: Cytokine Assaysmentioning
confidence: 99%